Financial innovation and Consumption in the United Kingdom - Bayoumi, Tamim (IMF Working Papers; Working Paper, 1990)
The last decade has seen widespread deregulation of domestic financial markets in the United Kingdom. This paper uses regional household data to investigate the connection between consumption and financial innovation. It is concluded that deregulation has led to a significant increase in the forward looking nature of consumption.